2020
DOI: 10.3390/d12020079
|View full text |Cite
|
Sign up to set email alerts
|

A Snap-Shot of Domatial Mite Diversity of Coffea arabica in Comparison to the Adjacent Umtamvuna Forest in South Africa

Abstract: Some plant species possess structures known as leaf domatia, which house mites. The association between domatia-bearing plants and mites has been proposed to be mutualistic, and has been found to be important in species of economic value, such as grapes, cotton, avocado and coffee. This is because leaf domatia affect the distribution, diversity and abundance of predatory and mycophagous mites found on the leaf surface. As a result, plants are thought to benefit from increased defence against pathogens and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In turn, other mite species are beneficial as they are predators and control harmful pest species. Situngu et al [7] focused on the diversity and composition of mites on an economically important plant host (Coffea aribica) compared to mites found in a neighbouring natural forest in South Africa. Their results showed that the coffee plantations were associated with only predatory mites, some of which are indigenous to South Africa.…”
mentioning
confidence: 99%
“…In turn, other mite species are beneficial as they are predators and control harmful pest species. Situngu et al [7] focused on the diversity and composition of mites on an economically important plant host (Coffea aribica) compared to mites found in a neighbouring natural forest in South Africa. Their results showed that the coffee plantations were associated with only predatory mites, some of which are indigenous to South Africa.…”
mentioning
confidence: 99%